(untitled) (Eurasian Research Bulletin, 2023)
To manage competitiveness, an objective assessment tool is required. An error in choosing a measurement method can lead to the adoption of erroneous management decisions. The article summarizes the views of the scientific community on features of the development of industrial enterprises in current market conditions, and the need to attract modern innovative technologies as a component in increasing their competitiveness. In determining the level of competitiveness of enterprises, it has been suggested to take into account factors determining the level of information reliability and weapons.